SPORADIC INCLUSION BODY MYOSITIS – SINGLE CENTER CASE SERIES OF 8 PATIENTS FROM A-FIFTEEN-YEAR PERIOD: Sporadični miozitis sa inkluzivnim telašcima - serija slučajeva - Aleksic, Dejan; Božović, Ivo; Kezić, Ivana; Gluščević, Sanja; Basta, Ivana; Rakočević-Stojanović, Vidosava (Medicinska istraživanja, 2025)
OBJECTIVE: Sporadic inclusion body myositis (sIBM) is the slowly progressive inflammatory myopathy. Clinical presentation comprises asymmetric distal and proximal limb weakness and dysphagia. Muscle biopsy showing rimmed vacuoles are the main diagnostic indicator. METHOD: We showed 8 patients with a sIBM at the Neurology Clinic of the University Clinical Center Serbia in the period 2009-2024. We analyzed medical records and following characteristics: sociodemographic, age and signs at onset of disease, co-morbidities, neurological examination, an IBM functional rating score, analysis of laboratory and diagnostic procedures. RESULTS: The average age of years at the onset of the disease was 57.7±0.4 years. The first signs of disease were difficulty walking, dysphagia, hand weakness and eyelid ptosis. The average IBMFRS was 28.7±7.8. Three patients had clinical and ENG signs for polyneuropathy. For four patient MRI showed muscle degenerative changes of grade 2b. Muscle biopsy was performed in seven patients and they fulfilled the criteria for clinically defined sIBM. The five patients were treated with IVIG with minimal and short-term improvement. CONCLUSION: Clinical examination and muscle biopsy are paramount in making the diagnosis of sIBM. Early diagnosis and early administration of the right therapy would make the greatest contribution to slowing the progression of the disease.